(untitled) (Al-Mukhtar Journal of Legal Science, 2024)
Arbitration is highlighted as a preferred method for dispute resolution due to its speed, low costs, confidentiality, the continuation of relationships between parties, avoiding the constraints and complex procedures of the judiciary. This does not mean neglecting disputes and the resulting arbitral awards, nor excluding judicial review. Arbitration procedures may be flawed or erroneous due to the arbitrators, leading to a defective award, necessitating an authority to restore order. Therefore, it is essential to subject the arbitral award to judicial review to ensure its correctness. This review is partially embodied in the annulment lawsuit, which is the subject of this paper.